Micro-climatic variations across Malawi have a greater influence on maize susceptibility to aflatoxins than to fumonisins - Ng'ambi, J.T.; Atehnkeng, J.; Monjerezi, M.; Ngongondo, C.; Vunain, E.; Ching’anda, C.; Ortega Beltran, A.; Cotty, P.J.; Matumba, L.; Bandyopadhyay, R. (Springer, 2023)
This study reports levels of aflatoxin and fumonisin in maize samples (n = 1294) from all agroecological zones (AEZs) in Malawi. Most maize samples (> 75%) were contaminated with aflatoxins and 45% with fumonisins, which co-occurred in 38% of the samples. Total aflatoxins varied across the AEZs, according to mean annual temperature (P < 0.05) of the AEZs. Samples from the lower Shire AEZ (median = 20.8 µg/kg) had higher levels of aflatoxins (P < 0.05) than those from the other AEZs (median = 3.0 µg/kg). Additionally, the majority (75%) of the positive samples from the lower Shire AEZ had aflatoxin levels exceeding the EU regulatory limit (4 µg/kg), whereas 25%, 37%, and 39% of positive samples exceeded the threshold in the mid-elevation, Lake Shore and upper and middle Shire, and highlands AEZs, respectively. The lower Shire AEZ is characterised by higher mean temperatures throughout the year and low erratic rainfall. However, total fumonisins did not show significant variation across AEZs, but all positive samples exceeded 150 µg/kg, required for tolerable daily intake of 1.0 µg/kg body weight per day, established by the European Food Safety Authority Panel on Contaminants in the Food Chain. Therefore, results of this study suggest that contamination of maize with aflatoxin responds to micro-climate more than with fumonisins. In addition, the data will be useful to public health policy-makers and stakeholders to articulate and implement monitoring and mitigation programs.